Physical Activities and Psychological Needs of Physical Education Students - Wang, Xiaopeng (International Journal of Social Sciences and Public Administration, 2024)
The study examined the levels of physical activity and psychological needs of students enrolled in physical education at Tangshan Normal University. The respondent profile indicated that the sample consisted mainly of female, first-year students aged 17-18, with the majority having a healthy BMI. In terms of physical activity, the pupils exhibited proficient fundamental movement abilities and independence in structuring their fitness regimens. Nevertheless, certain areas that may be enhanced were identified, including the decision to opt for stairs. The analysis revealed no statistically significant differences in the levels of physicalactivity among the students based on their sex, age, BMI, or year level. Regarding psychological needs, the students expressed a robust sense of autonomy, experiencing a sense of freedom to independently make important life choices. Nevertheless, their perceptions of opportunities for self-determination in daily life were somewhat diminished. Regarding competence, pupils experienced acknowledgment from others for their abilities.